2018
DOI: 10.2147/ott.s171242
|View full text |Cite
|
Sign up to set email alerts
|

Combined detection of IL-6 and IL-8 is beneficial to the diagnosis of early stage esophageal squamous cell cancer: a preliminary study based on the screening of serum markers using protein chips

Abstract: BackgroundThe diagnosis rate of early stage esophageal squamous cell carcinoma (ESCC) is low due to the lack of specific tumor markers. Seeking for these markers is beneficial to improve the early diagnosis rate and the prognosis of patients. This study profiles the differentially expressed proteins of early stage ESCC patients via the AAH-BLG-507 protein chip, which further consolidates the clinical evidence of ESCC diagnosis.Materials and methodsIn this study, 20 serum samples were collected from Taihe Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…On the contrast, Łukaszewicz-Zając et al found a stronger predictive value of IL-6 as compared to carcinoembryonic antigen (CEA) levels in EAC patients without chemotherapy [17]. This is in line with data obtained from ESCCs and other gastrointestinal malignancies indicating an association with increased tumor stage and poor prognosis [8][9][10][11][12][13]. In summary, our data support the role of systemic IL-6 levels as potential biomarker in patients with EACs although a distinct stratification for clinicopathological values or an association with overall survival was not found.…”
Section: Plos Onementioning
confidence: 52%
See 1 more Smart Citation
“…On the contrast, Łukaszewicz-Zając et al found a stronger predictive value of IL-6 as compared to carcinoembryonic antigen (CEA) levels in EAC patients without chemotherapy [17]. This is in line with data obtained from ESCCs and other gastrointestinal malignancies indicating an association with increased tumor stage and poor prognosis [8][9][10][11][12][13]. In summary, our data support the role of systemic IL-6 levels as potential biomarker in patients with EACs although a distinct stratification for clinicopathological values or an association with overall survival was not found.…”
Section: Plos Onementioning
confidence: 52%
“…Proinflammatory cytokines like interleukin-(IL-) 6 or IL-2 mainly attract and activate other inflammatory cells in the tumor microenvironment [5][6][7]. Both interleukins have been reported to play a role in esophageal squamous cell carcinomas (ESCC) and other gastrointestinal malignancies like gastric cancers [8][9][10][11][12][13][14][15]. However in EACs conflicting results have been reported [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…2017), which could reverse the changes of cytochrome P450 enzyme activity, and ultrastructure in rats induced by CCl 4 , showing a strong liver preservation effect (Wang et al. 2018) through its antioxidant activities. Although several pharmacological activities of anthraquinones have been reported (He et al.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the current diagnosis rate of early EC is low, and EC-specific markers are lacking. Furthermore, our previous study found that serum IL-6 and IL-8 may be an effective indicator for the early diagnosis of ESCC, but the clinical application needs further investigation 6…”
Section: Introductionmentioning
confidence: 97%